1981
DOI: 10.1136/hrt.46.6.657
|View full text |Cite
|
Sign up to set email alerts
|

Transseptal pressure gradient with leftward septal displacement during the Mueller manoeuvre in man.

Abstract: Septal displacement is postulated as an important mediator of ventricular interdependence. During acute right ventricular loading with the Mueller manoeuvre the septum flattens and shifts leftward. To investigate the mechanism of this septal deformation, we measured transseptal pressures in nine patients during Mueller manoeuvres with simultaneous right and left ventricular micromanometers, and left ventricular configuration with two-dimensional echocardiograms. Data were analysed throughout diastole and at en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(27 citation statements)
references
References 19 publications
6
20
1
Order By: Relevance
“…These changes were far less striking than the end-diastolic flattening seen during bypass or cardiac arrest, but are consistent with findings of previous studies that indicated persistent septal flattening throughout several cardiac cycles.1 2 Why the septum maintains its flat configuration during systole when the left ventricular cavity pressure greatly exceeds right ventricular pressure is not known. As ventricular contraction proceeds, the stiffness of the muscle increases above the level present during diastole, when it is more flaccid.9' 10 Thus, one possible explanation for the persistent systolic flattening is that the increase in stiffness in the initially flattened septum is enough to counterbalance the increase in left-to-right forces tending to push the septum toward the right ventricle.…”
Section: Resultssupporting
confidence: 89%
“…These changes were far less striking than the end-diastolic flattening seen during bypass or cardiac arrest, but are consistent with findings of previous studies that indicated persistent septal flattening throughout several cardiac cycles.1 2 Why the septum maintains its flat configuration during systole when the left ventricular cavity pressure greatly exceeds right ventricular pressure is not known. As ventricular contraction proceeds, the stiffness of the muscle increases above the level present during diastole, when it is more flaccid.9' 10 Thus, one possible explanation for the persistent systolic flattening is that the increase in stiffness in the initially flattened septum is enough to counterbalance the increase in left-to-right forces tending to push the septum toward the right ventricle.…”
Section: Resultssupporting
confidence: 89%
“…These results are similar to those we previously reported1' in experiments during pulmonary artery constriction, are similar to the studies of others, 3,20,2' and are in general agreement with our current understanding of diastolic septal mechanics. [25][26][27] The importance of the contribution of pericardial constraint to the mechanism of the shift has been emphasized previously; opening the pericardium results in less septal shift than occurs while the pericardium is intact.1 7} 28 Our data differ from those in a recent report that concluded that septal shift was not an important factor in the reduction of LV volume in dogs with pulmonary vascular injury induced by glass beads." The degree of elevation of RV diastolic pressure in that study suggests that a septal shift was not observed because the increase in RV afterload was not as great as that produced by the repeated embolization in our study.…”
Section: Transseptal Pressure Gradientcontrasting
confidence: 57%
“…12 13 The increase in the right atrial "x" descent reflects a "suction" effect transmitted to the slack atrium after atrial systole by the strongly negative intrathoracic pressure. The right ventricular to right atrial pressure difference was therefore greater during the Mueller maneuver and this, along with the altered right Vol.…”
Section: Discussionmentioning
confidence: 99%